2004
DOI: 10.1300/j050v14n01_03
|View full text |Cite
|
Sign up to set email alerts
|

International and Local Student Satisfaction: Resources and Capabilities Perspective

Abstract: In this paper, we develop a conceptual model for assessing student satisfaction with universities and the likelihood of students recommending their institutions to other prospective students. Student satisfaction is conceptualised as a mediator between resources and capabilities and recommendation. The resources and capabilities that contribute to student satisfaction are identified as teaching, learning, technology, library, student services and student orientation. The resource needs of local and internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(138 citation statements)
references
References 38 publications
4
128
0
6
Order By: Relevance
“…Student satisfaction is being shaped continually by repeated experiences in campus life". Current research findings reveal that satisfied students may attract new students by engaging in positive word-of-mouth communication to inform acquaintances and friends and they may return to the university to take other courses (Guolla, 1999;Wiers-Jenssen et al, 2002;Mavondo et al, 2004;Schertzer & Schertzer, 2004;Marzo-Navarro et al, 2005ab;Helgesen & Nesset, to learning. Finally, Elliott & Shin (2002) showed that student satisfaction has also a positive impact on fundraising and student motivation.…”
Section: Service Quality and Satisfaction In Higher Educationmentioning
confidence: 94%
“…Student satisfaction is being shaped continually by repeated experiences in campus life". Current research findings reveal that satisfied students may attract new students by engaging in positive word-of-mouth communication to inform acquaintances and friends and they may return to the university to take other courses (Guolla, 1999;Wiers-Jenssen et al, 2002;Mavondo et al, 2004;Schertzer & Schertzer, 2004;Marzo-Navarro et al, 2005ab;Helgesen & Nesset, to learning. Finally, Elliott & Shin (2002) showed that student satisfaction has also a positive impact on fundraising and student motivation.…”
Section: Service Quality and Satisfaction In Higher Educationmentioning
confidence: 94%
“…International students had an understanding and interpretations of service quality that is different from that of national students where this understanding and interpretations had an effect on their level of satisfaction (Ansary & Jayashree, 2014;Mavondo, Tsarenko, & Gabbott, 2004). According to Humphries, Rauh, and McDine (2013), satisfaction remained high in Canada for international students, showing that 90% of students are either satisfied or extremely satisfied.…”
Section: Service Quality and Satisfactionmentioning
confidence: 99%
“…al, 2005). High levels of student loyalty have also been found to lead to repeat purchase through continuing education (Mavondo et al 2004). …”
Section: Student Loyaltymentioning
confidence: 99%